Max/Msp sebagai Medium Perluasan Perspektif Komponis pada Karya Musik Masa Kini - Candra Bangun Setyawan (Institut Seni Indonesia Denpasar, 2020)
Purpose: This study is to understand the integration of music and technology that has broadened various perspectives in representing experiences into musical works. Research methods: This article is a literature review about Max/Msp. It is a software based visual programming language for music and multimedia. Results and discussion: The emergence of Max offers a variety of possibilities related to the space of creativity, as well as having an impact on the loss of the boundaries of the creativity process. On the other hand, from the many possibilities that can be offered, access and availability of books related to Max are still very limited in Indonesia. Implication: Max contributes in expanding musical works through various new perspectives.